PENGARUH CONTENT MARKETING, INFLUENCER MARKETING, DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN PADA TOKO KASYARAA DI KABUPATEN BADUNG - Ni Putu Sri Dewi; Ni Nyoman Suriani; I Made Yogiarta (Fakultas Ekonomi Universitas Warmadewa, 2024)
This study aims to explore the importance of implementing content marketing strategies, influencer marketing, and product quality in increasing consumer buying interest in Toko Kasyaraa products in Badung Regency. The targeted population includes all consumers of Toko Kasyaraa with an infinite number. Through determining the sample through purposive sampling and the Hair et al. formula, a total of 90 consumers who have purchased Toko Kasyaraa products were obtained. Data was empirically collected through a questionnaire distribution procedure and analysed through a multiple linear regression approach. The study results confirmed that engaging and relevant content was found to encourage consumers to make product purchases. Furthermore, the use of influencers with good communication skills was found to increase the attractiveness of consumers to make purchases. Good quality products also play an important role in consumers' decision-making to purchase products. This research is able to contribute theoretically to marketing literature and practically for Toko Kasyaraa to strive to improve the quality of the products offered, increase online marketing activities, especially in uploading interesting content, and by presenting influencers in promoting products.